(untitled) (Journal of Contemporary Philology, 2025)
This article constitutes the second part of a two-part study on event modality in selected Turkish varieties spoken in Kosovo, North Macedonia, Bulgaria, and Eastern Thrace (Turkey). Building on the analysis of expressions of possibility and necessity in Part 1, this part investigates expressions of volitive modality and their intra- and inter-dialectal variation in Western Rumelian Turkish and Eastern Rumelian Turkish contextualizing the dialectological data with reference to Modern Standard Turkish and Ottoman Turkish varieties. In addition to the consideration of lexical and semantic features, special attention is given to the complementation patterns, which involve both non-finite and finite linking strategies. The Balkan Turkish data will be discussed within the three-dimensional framework of heritage, universal tendencies, and language contact. The survey at the end of this part summarizes and compares the main findings of the study on expressions of possibility, necessity, and volition, and evaluate these findings in the context of Balkan linguistic.